ANALISIS SOLIDARITAS SOSIAL MEKANIK PADA ETNIS MADURA DAN MELAYU DI KELURAHAN SIANTAN TENGAH KECAMATAN PONTIANAK UTARA - Jumiliani Jumiliani; Fatmawati Fatmawati; Iwan Ramadhan (Universitas Tanjungpura, 2021)
ABSTRACTThis study aims to determine the social mechanical sosilidarity of the Madurese and Malay ethnicities in Siantan Tengah Village, North Pontianak District. The general problem in this research is